The ZNF217 Biomarker Predicts Low- and High-Risk Oncotype DX® Recurrence Score in ER-Positive Invasive Breast Cancers - Cohen, Pascale A.; Loudig, Olivier; Liu, Christina; Albanese, Joseph; Fineberg, Susan (Frontiers in Pharmacology, 2019)
We assessed mRNA and protein expression levels of the ZN217 oncogene in 17 clinical FFPE ER-positive invasive breast cancer specimens with known (low or high) Oncotype DX® Recurrence Scores. This study shows that mRNA or nuclear protein levels of the ZNF217 significantly correlate with Oncotype DX® Recurrence Score.